Optimization of Accelerometer Sensor Location In Arch Bridge Monitoring System Using The Sensor Elimination Using Capital Assurance Criterion (SEAMAC) Method - Ritonga, Qonita; Kurniawan, Mahadi; Syarif, Firman; Rachmat Setiawan, Panji; Ahmadi , Heri; Raveena Putri, Citra; Oktavia, Ferly (UIR Press, 2025)
In developing countries such as Indonesia, various fields of construction are currently being actively developed, especially bridge construction. Damage to the bridge structure itself requires very large repair costs. Currently, a monitoring system is being introduced to assess the condition of structures against dynamic loads, namely SHMS (Structural Health Monitoring System). The research aims to determine Finite Element Modeling, the optimal location, and several accelerometer sensors. To determine the condition of the arch bridge structure, it is necessary to detect damage through the results of the structural response recorded via the accelerometer sensor. In identifying the optimum number and location of sensors, the method used in this research is SEAMAC (Sensor Elimination Using Modal Assurance Criterion). Where this method is an algorithm method that performs an elimination on the sensor. The optimal placement of accelerometer sensors is determined using the Sensor Elimination Using Modal Assurance Criterion (SEAMAC) method, focusing on the floor plate and the bridge arch frame. Proper sensor placement is crucial as it yields important location data essential for identifying the modal characteristics of the bridge structure. In total, 16 accelerometer sensor locations were identified, with 8 sensors designated for both the floor plate and the arch frame.